Serum Lipids and Plasma Glucose in Women on Hormonal-Based Contraceptives - Abdullahi, H.L.*, Saleh, A.A., Mohammed, I.Y., Yahaya, I.S., Abdullahi, T.M. (Sokoto Journal of Medical Laboratory Science)
Hormonal-based contraceptives (HCs) available as oral (OCs) and injectable (ICs), have gained wide acceptance worldwide including developing countries like Nigeria due to their high efficacy in preventing pregnancy. However, they are associated with increased risks for certain metabolic diseases. In this study, a total of 200 participants were randomly recruited for the study made up of 100 women on contraceptive (subjects) and 100 non-contraceptive users (controls) The mean age and BMI of the subjects was 28.97 ± 7.18 years and 24.61 ± 5.30 respectively. There were significant differences (p<0.05) between the mean values of fasting glucose (FG) (4.58 ± 1.10 mmol/L vs. 3.9 ± 0.57mmol/l), total cholesterol (TC) (4.75 ± 0.68mmol/L vs. 3.98 ± 0.74 mmol/L), triglyceride (TG) (1.16 ± 0.28mmol/L vs. 1.35 ± 0.31mmol/L), high density lipoprotein(HDL-C) (1.62 ± 0.35mmol/L vs. 1.13 ± 0.33mmol/L) and low density lipoprotein(LDL-C) (2.65 ± 045mmol/L vs. 2.14 ± 0.59mmol/L) of women on HCPs and that of control group. No significant differences (p>0.05) were observed between the mean values of plasma FG (6.94 ± 6.85mmol/L vs. 5.15 ± 1.20mmol/L), serum TC (5.72 ± 1.53mmol/L vs. 5.23 ± 1.24mmol/L), serum TG (1.19 ± 0.98mmol/l vs. 1.14 ± 0.82mmol/l) as well as serum LDL-C (3.47 ± 1.28mmol/l vs. 3.41 ± 1.21mmol/L) of OC and IC users respectively. However, a significant difference was observed between mean values of serum HDL-C (1.70 ± 0.73mmol/l vs. 1.37 ± 0.37mmol/l respectively) between OC and IC users. No significant difference (p<0.05) was observed on the basis of duration of use of HCs. The results of this study further emphasize the need for caution and routine regular check-up when using HCs in order to prevent complications and the adverse side effects associated with their use.